Antileishmanial, Antimalarial and Antimicrobial activity of the Jamaican ‘Touch-me-not’ sponge Neofibularia nolitangere - Monique N. Thompson and Winklet Gallimore (Journal of Applied Pharmaceutical Science, 2013)
The crude extracts and fractions of the Jamaican sponge Neofibularia nolitangere were examined for biological activity. The dried animal was extracted successively in three organic solvents (hexane, methylene chloride and methanol) and tested for their potential as antileishmanial, antimalarial and antimicrobial agents. Fractions of the crude methylene chloride extract demonstrated notable antimalarial properties giving percentage inhibitions of 87% and 78% respectively for fractions Y4 and Y5 at 20 μg/mL. Fractions Y4 and Z4 showed remarkable antileishmanial activity inhibiting the growth of the pathogen by 93.31% and 91.77% respectively at 20 μg/mL. No significant activity was observed in the antimicrobial assays.
Keywords: Neofibularia nolitangere, antilei